The Purchase Decision of The Muslimah Generation Y and Z to Halal Cosmetic Product: Analysis of DSN-MUI Fatwa Number 26 of 2013 - Jaenudin; Cucu Susilawati; Rosi Hasna Sari; Adang Sonjaya (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This study aims to determine the implementation of the DSN MUI fatwa Number 26 of 2013. Furthermore, how it affects the purchase decision of Generation Muslimah Y and Z in choosing and buying cosmetic products—using qualitative methods with triangulation techniques, namely using various data collection methods consisting of observations, interviews, questionnaires, and documentation studies. The results show that the critical point of halal in cosmetics consists of the composition of the ingredients used and the resistance of cosmetics to water. Among the Muslim generations Y and Z, some already know, and some do not know the halal standards of cosmetics. However, according to Generations Y and Z, cosmetic halal standards in DSN – MUI Fatwa Number 26 of 2013 can affect their purchase decision on halal cosmetic products. Halal certification is still the main reason for purchasing halal cosmetics compared to prices, trends, and brands. It did by the Muslimah Generation Y and Z. In conclusion, DSN Fatwa–MUI Number 26 of 2013 applies effectively to The Muslimah Generation Y and Z as a consideration in choosing and buying halal cosmetics. This research implies that halal labeling can be used as a marketing strategy for a cosmetic product. The originality of this research lies in the object of research, which is only limited to Generations of Muslim women Y and Z and Fatwa DSN MUI Number 26 of 2013 as an analytical tool.